Exploiting the role of T cells in the pathogenesis of Sjögren’s syndrome for therapeutic treatment - An, Qi; Zhao, Jingwen; Zhu, Xueqing; Yang, Baoqi; Wu, Zewen; Su, Yazhen; Zhang, Liyun; Xu, Ke; Ma, Dan (Frontiers in Immunology, 2022)
Sjögrens syndrome (SS) is caused by autoantibodies that attack proprioceptive salivary and lacrimal gland tissues. Damage to the glands leads to dry mouth and eyes and affects multiple systems and organs. In severe cases, SS is life-threatening because it can lead to interstitial lung disease, renal insufficiency, and lymphoma. Histological examination of the labial minor salivary glands of patients with SS reveals focal lymphocyte aggregation of T and B cells. More studies have been conducted on the role of B cells in the pathogenesis of SS, whereas the role of T cells has only recently attracted the attention of researchers. This review focusses on the role of various populations of T cells in the pathogenesis of SS and the progress made in research to therapeutically targeting T cells for the treatment of patients with SS.